The territories of identity : architecture in the age of evolving globalisation - Bandyopadhyay, Soumyen; Garma Montiel, Guillermo (London ; Routledge, 2013)
'The construction and representation of meaning through the interplay of place making, art and architecture, and collective memory have always given shape to the expressive intent of designers and consequently, has embodied identity within the built environment. This book explores the relationship between identity in architecture and the related themes of place, memory and representation. It does so by examining the nature of their intersections and transgressions of their traditional boundaries within evolving globalisation. The expedited globalised process of exchange and new forms of cultural production have transformed old established notions of identity, calling into question their conceptual foundations. This book explores the spatial and representational dimension of this phenomenon, by addressing how the reshaping of the key themes of place, architecture and memory are altering the nature, as well as, our understanding of identity. Cutting across boundaries, the book drives discussion of identity beyond the well-worn concern for its loss within a globalised context, and importantly provides links between identity, place, memory and representation in architecture. It addresses such issues as architecture technology, place and memory - critical issues in the monitoring and mapping of identity shift within a rapidly globalising context. Including a range of case studies and with contributions from eminent individuals, this book presents fresh insights and diverse perspectives on the evolving question of identity and globalisation'--
Includes bibliographical references (pages 204-220) and index.
Keywords: Architecture and globalization; Culture and globalization